Pengembangan Potensi Wisata Embung Sumberagung Melalui Revitalisasi Atraksi Wisata - Alyaa’ Chiquita Fairuzara A. R.; Kezia Angelin Patricia; Nathania Trixie Aryanti (STIKes Ibnu Sina Ajibarang, 2023)
The problem faced by the village community is the lack of knowledge about the existing tourism potential, this causes the existing tourism potential to not develop and causes the environment around this tourism potential to be neglected. Because the community lacks concern for existing tourism potential because there is no attraction from tourism potential so that village communities to promote existing tourism potential are lacking. Making tourist attractions in the form of photo spots as a form of tourism village development, is carried out using the participation and socialization approach to the community, through the creation of photo spots which were inaugurated during the